Evaluasi keberhasilan pengisian saluran akar dengan sediaan zinc oxide eugenol dan campuran calcium hydroxide dengan pasta iodoform - Luh Wayan Ayu Rahaswanti (DiscoverSys Inc., 2017)
Aim: the aim of this study was to investigate the succesful rate between Zinc Oxide Eugenol and Calcium Hydroxide with Iodoform Paste as root canal sealer for necrotic primary teeth. Method: pulpectomy procedures were conducted on 16 maxilary anterior teeth and for the obturation step, they were devided into two groups consist of 8 teeth. The first group of teeth were obturated with Zinc Oxide Eugenol sealer and the second group were obturated with Calcium Hydroxide with Iodoform Paste sealer. The data was taken on one month, two months, and three months after the treatment and then analized with Fisher’s Exact Test. Result: the result shows that there is no significant succesful rate between Zinc Oxide Eugenol and Calcium Hydroxide with Iodoform Paste as root canal sealer for necrotic primary teeth. Conclusion: the conclusion of this study is that both of Zinc Oxide Eugenol and Calcium Hydroxide with Iodoform Paste have similar efficacy in treating necrotic primary teeth.